Resourcefulness matters: Student patterns for coping with structural and academic challenges - Dison, L.; Shalem, Y.; Langsford, D. (South African Journal of Higher Education, 2019)
There is general agreement that there are many structural constraints beyond students’ control which influence the degree of success that students can attain as they learn to participate in academic practice. Less understood are the patterns of students’ experiences of the socio-economic environment of their schooling and university, their views of the enabling and constraining conditions of learning and their perceptions of their agency in overcoming these conditions. The data for our study were collected through a questionnaire survey of 591 Bachelor of Education students across three years of the degree at a South African University. Several patterns of resourcefulness and levels of articulation emerged which reveal complex sets of experiences and strategies as students reflect on adversities and challenges they encountered at school and at university. We argue for an in depth understanding of the nature of student agency which recognises its role in shaping their engagement with material, social, academic and affective challenges.